2019
DOI: 10.1007/s40534-019-00197-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adverse weather on drivers’ perceived risk during car following based on driving simulations

Abstract: Adverse weather has a considerable impact on the behavior of drivers, which puts vehicles and drivers in hazardous situations that can easily cause traffic accidents. This research examines how drivers' perceived risk changes during car following under different adverse weather conditions by using driving simulation experiment. An expressway road scenario was built in a driving simulator. Eleven types of weather conditions, including clear sky, four levels of fog, four levels of rain and two levels of snow, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Driving in heavy rain is also quite dangerous due to reduced visibility of the drivers. The worsening weather conditions, such as heavy rain, etc., have significant effect on increasing drivers' perceived risk due to limited visibility (Chen et al, 2019). This is in line with research related to situation awareness in different road environments (Salmon et al, 2014).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Driving in heavy rain is also quite dangerous due to reduced visibility of the drivers. The worsening weather conditions, such as heavy rain, etc., have significant effect on increasing drivers' perceived risk due to limited visibility (Chen et al, 2019). This is in line with research related to situation awareness in different road environments (Salmon et al, 2014).…”
Section: Introductionsupporting
confidence: 84%
“…Several situation scenarios that may affect driver's intention to violate traffic signs can also be added as shown in Table 1. Human-related factors can be specified into four aspects, that is, "No Police Officers" (Purnamasari, 2019;Purnamasari & Ansusanto, 2017;Winarso, 2016), "In A Hurry" (Purnamasari, 2019;Purnamasari & Ansusanto, 2017;Winarso, 2016), "Imitate Mistakes" (Purnamasari, 2019;Purnamasari & Ansusanto, 2017;Winarso, 2016) and "Sleep Deprivation & Fatigue" (Ho et al, 2015;Ho & Widaningrum, 2016;Sanjaya et al, 2018;Wijayanto et al, 2018) while environmental-related factors can be specified into 3 aspects, that is, "Quiet Roads" (Salmon et al, 2014), "Night Driving" (Setyaningsih et al, 2018) and "Driving in Heavy Rain" (Chen et al, 2019;Salmon et al, 2014). This study analyzed the influence factors of traffic signs violation based on several situation scenarios by well-educated young drivers in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Putting formulas (4) and (5) into formula (3), the state space model of CAVs within the fleet can be written as…”
Section: Model Formulation 221 E State Space Model Of Cavsmentioning
confidence: 99%
“…erefore, the driver tends to continue driving until the following distance is equal to or less than the safety distance. After realizing the crash-prone traffic condition, the driver will operate the vehicle with sequential rushed acceleration or nasty deceleration to keep out of traffic accidents [5]. Furthermore, the researchers found that most drivers prefer to drive at high speeds when they cannot see the vehicle in front.…”
Section: Introductionmentioning
confidence: 99%
“…Quddus et al proposed a data-driven approach with the help of VISSIM platform to estimate the traffic collision probability [17]. Pan et al extracted vehicle trajectory information by scanning street scenes with the help of Lidar and camera data [18]. Huang et al proposed a force-based heterogeneous traffic simulation model to identify dangerous behaviors of various roadway user, which may trigger traffic accident in real world [19].…”
Section: Introductionmentioning
confidence: 99%